Editorial: Nanomaterials to combat pathogenic microorganisms - Alavi, Mehran; Kahrizi, Danial; Martinez, Fleming; Rai, Mahendra (Frontiers in Microbiology, 2023)
In the present scenario, there are frightening reports of new and emerging microbial pathogens such as SARS-CoV-2 has threatened human health globally causing the outbreak of disease (1). In addition, some studies indicate the development of resistance in pathogenic microbes, for example, Candida auris has become a global threat evidenced by high mortality due to the development of resistance to different antimicrobials.